Tripartite split-GFP assay to identify selective intracellular nanobody that suppresses GTPase RHOA subfamily downstream signaling - Keller, Laura; Tardy, Claudine; Ligat, Laetitia; Le Pennec, Soazig; Bery, Nicolas; Koraïchi, Faten; Chinestra, Patrick; David, Mélissa; Gence, Rémi; Favre, Gilles; Cabantous, Stéphanie; Olichon, Aurélien (Frontiers in Immunology, 2022)
Strategies based on intracellular expression of artificial binding domains present several advantages over manipulating nucleic acid expression or the use of small molecule inhibitors. Intracellularly-functional nanobodies can be considered as promising macrodrugs to study key signaling pathways by interfering with protein-protein interactions. With the aim of studying the RAS-related small GTPase RHOA family, we previously isolated, from a synthetic phage display library, nanobodies selective towards the GTP-bound conformation of RHOA subfamily proteins that lack selectivity between the highly conserved RHOA-like and RAC subfamilies of GTPases. To identify RHOA/ROCK pathway inhibitory intracellular nanobodies, we implemented a stringent, subtractive phage display selection towards RHOA-GTP followed by a phenotypic screen based on F-actin fiber loss. Intracellular interaction and intracellular selectivity between RHOA and RAC1 proteins was demonstrated by adapting the sensitive intracellular protein-protein interaction reporter based on the tripartite split-GFP method. This strategy led us to identify a functional intracellular nanobody, hereafter named RH28, that does not cross-react with the close RAC subfamily and blocks/disrupts the RHOA/ROCK signaling pathway in several cell lines without further engineering or functionalization. We confirmed these results by showing, using SPR assays, the high specificity of the RH28 nanobody towards the GTP-bound conformation of RHOA subfamily GTPases. In the metastatic melanoma cell line WM266-4, RH28 expression triggered an elongated cellular phenotype associated with a loss of cellular contraction properties, demonstrating the efficient intracellular blocking of RHOA/B/C proteins downstream interactions without the need of manipulating endogenous gene expression. This work paves the way for future therapeutic strategies based on protein-protein interaction disruption with intracellular antibodies.